2008
DOI: 10.1055/s-0028-1091396
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Vaginal Misoprostol versus Cervical Foley Plus Oral Misoprostol for Cervical Ripening and Labor Induction

Abstract: We compared labor induced by vaginal misoprostol versus a supracervical Foley catheter and oral misoprostol. Singleton pregnancies at > or = 24 weeks' gestation were randomized to either an initial 25-microg dose of intravaginal misoprostol, followed by 50-microg intravaginal doses at 3- to 6-hour intervals, or a supracervical Foley balloon and 100 microg of oral misoprostol at 4- to 6-hour intervals. Primary outcome was time from induction to delivery. One hundred twenty-six women were randomized to vaginal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 9 publications
6
55
2
Order By: Relevance
“…About neonatal indices, the two groups were comparable as there was no significant difference in outcome. This favorable outcome has been documented in studies evaluating the efficacy of various methods of induction combining pharmacological and mechanical techniques [12,14,15].…”
Section: Discussionmentioning
confidence: 93%
“…About neonatal indices, the two groups were comparable as there was no significant difference in outcome. This favorable outcome has been documented in studies evaluating the efficacy of various methods of induction combining pharmacological and mechanical techniques [12,14,15].…”
Section: Discussionmentioning
confidence: 93%
“…The Foley bulb was placed just above the level of the internal os and inflated with 60cc of sterile water. 6, 7, 11, 14 The catheter was taped to the inner thigh with gentle traction and deflated and removed after 12 hours if still in place. The oxytocin protocol was initiated once the Foley bulb was no longer in place (Appendix 2, http://links.lww.com/xxx).…”
Section: Methodsmentioning
confidence: 99%
“…3, 4 Plausibly, combining both mechanical and pharmacologic methods may have a synergistic effect in achieving labor. Some studies have shown promise in reducing labor time and risk of cesarean delivery with combination methods, 6, 7 while others have not. 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…6 Multiple studies have shown no consistent association between Foley catheter use and these risks, although is it generally accepted that low-lying placenta is a relative contraindication for Foley catheter placement because of concern for potential disruption of the placental edge resulting in maternal hemorrhage. [7][8][9][10][11][12][13] Embrey and Mollison 14 first described the use of a transcervical Foley catheter for labor induction in 1967 using a 26 gauge Foley with a 50-mL balloon. Since this initial study, balloon inflation sizes of 30 -80 mL have been reported in the literature with inconsistent results regarding induction-to-delivery duration and risk of cesarean delivery.…”
mentioning
confidence: 99%